National Survey of Black Americans, Waves 1-4, 1979-1980, 1987-1988, 1988-1989, 1992 - Jackson, James S. (James Sidney) ([Verlag nicht ermittelbar], 1996)
The purpose of this data collection was to provide an appropriate theoretical and empirical approach to concepts, measures, and methods in the study of Black Americans. Developed with input from social scientists, students, and a national advisory panel of Black scholars, the survey investigates neighborhood-community integration, services, crime and community contact, the role of religion and the church, physical and mental health, self-esteem, life satisfaction, employment, the effects of chronic unemployment, the effects of race on the job, interaction with family and friends, racial attitudes, race identity, group stereotypes, and race ideology. Demographic variables include education, marital status, income, employment status, occupation, and political behavior and affiliation.